Four primordial modes of tRNA-synthetase recognition, determined by the (G,C) operational code - Rodin, Sergei N. (The National Academy of Sciences of the USA, 1997)
In distinction to single-stranded anticodons built of G, C, A, and U bases, their presumable double-stranded precursors at the first three positions of the acceptor stem are composed almost invariably of G-C and C-G base pairs. Thus, the “second” operational RNA code responsible for correct aminoacylation seems to be a (G,C) code preceding the classic genetic code. Although historically rooted, the two codes were destined to diverge quite early. However, closer inspection revealed that two complementary catalytic domains of class I and class II aminoacyl-tRNA synthetases (aaRSs) multiplied by two, also complementary, G2-C71 and C2-G71 targets in tRNA acceptors, yield four (2 × 2) different modes of recognition. It appears therefore that the core four-column organization of the genetic code, associated with the most conservative central base of anticodons and codons, was in essence predetermined by these four recognition modes of the (G,C) operational code. The general conclusion follows that the genetic code per se looks like a “frozen accident” but only beyond the “2 × 2 = 4” scope. The four primordial modes of tRNA–aaRS recognition are amenable to direct experimental verification.